2020
DOI: 10.1177/2382120520973206
|View full text |Cite
|
Sign up to set email alerts
|

Medicine Residents are Unprepared to Effectively Treat Patients with Obesity: Results from a U.S. Internal Medicine Residency Survey

Abstract: Background: In an obesity epidemic, physicians are unprepared to treat patients with obesity. The objective of this study was to understand how obesity is currently addressed in United States (U.S.) Internal Medicine (IM) residency programs and benchmark the degree to which curricula incorporate topics pertaining to the recently developed Obesity Medicine Education Collaborative (OMEC) competencies. Methods: Invitations to complete an online survey were sent via postal mail to U.S IM residency programs in 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We based the family medicine survey on a similar survey of medical schools [ 22 ] and internal medicine residency programs [ 16 ]. To emphasize unique aspects of family medicine, the survey was adapted, through an iterative process, to include questions related to the prevention of obesity (in addition to its management), the extent to which programs integrate clinical and community systems as partners in obesity management, the degree to which patient-centered communication is emphasized, and the level of participation of other disciplines as part of the “medical home” team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We based the family medicine survey on a similar survey of medical schools [ 22 ] and internal medicine residency programs [ 16 ]. To emphasize unique aspects of family medicine, the survey was adapted, through an iterative process, to include questions related to the prevention of obesity (in addition to its management), the extent to which programs integrate clinical and community systems as partners in obesity management, the degree to which patient-centered communication is emphasized, and the level of participation of other disciplines as part of the “medical home” team.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to lack of sufficient clinic time and inconsistent reimbursement for obesity related codes [ 13 ], other reasons why primary care physicians may not effectively address obesity include discomfort discussing obesity with patients [ 14 ] and limited exposure to obesity as part of formal education in both medical school and residency. Studies have shown that less than one-third of medical schools meet the minimum recommended hours of nutrition education [ 15 ] and there is limited coverage of obesity-related topics in internal medicine programs [ 16 ] or medical licensing exams [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This problem, however, is not unique to primary care; physicians in various specialties also report the same challenges. [10][11][12][13][14] As such, it is plausible that educational content regarding management of patients with obesity may be best delivered during undergraduate medical education (UGME), rather than being reserved for postgraduate medical education. In fact, there is consensus in the literature that medical students should be taught approaches to management of patients with obesity; [14][15][16][17][18][19][20][21] however, there is a lack of understanding on how this topic is currently being taught at the UGME level in Canada and whether graduating students are competent in managing patients with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Although barriers to adequate obesity care exist at all levels of the medical system including lack of time and reimbursement, inadequate physician training remains an important obstacle [6,7]. Currently, up to one-fifth of internal medicine training programs, which are responsible for training primary care physicians who are at the frontlines of obesity care, provide very little instruction on physical activity and nutrition, and more than one-third provide very little or no instruction on psychosocial and behavioral components of obesity, weight stigma and discrimination [8]. In a national survey of primary care physicians in the United States, approximately 90% identified additional training in nutrition and physical activity counseling as a targetable intervention to improve obesity related care [9].…”
Section: Introductionmentioning
confidence: 99%